PENGARUH AKULTURASI BUDAYA MASYARAKAT LOLOAN TERHADAP STRUKTUR SYAIR BURDAH DI BALI - M, Riesta Maulidya; Sugiatmi, Fitria; Mabruri, M Alan (Melanesia : Jurnal Ilmiah Kajian Bahasa dan Sastra, 2018)
This study aims to describe the elements formation of Syair Burdah in Bali and describes the influence of cultural acculturation. Problem analyzed is the difference form in the composition of Syair Burdah in Bali as a result the acculturation of society culture. Theory used in analyzing are the critical discourse theory by Van Dijk. This theory helps to analyze theform of the structure in the Syair Burdah and external elements that influence it. The approach used is anthropolinguistics to analyze the diversity of structures and values in the Syair Burdah in Bali and cultural aspects. The type of research is qualitative by using words to describe the results of the analysis of Syair Burdah in Bali. From the results of the analysis it’s known that the form of Syair Burdah in Bali is influenced by other cultural elements such as Arab and Malay so the form of the Syair like separate but actually a whole unit.